Determining physiological and energetic demands during high-level pommel horse routines using a modified method based on heart rate-oxygen uptake functions - Seemann-Sinn, A.; Rüdrich, P.; Gorges, T.; Sandau, I.; Naundorf, F.; Wolfarth, B. (Sports, 2024)
This study aimed (1) to assess the validity of a modified method (Mmod) based on heart rate (HR)—oxygen uptake (VO2) regression functions to calculate total energy costs (Wtotal) and aerobic (Waer) and anaerobic alactic energy contribution (Wpcr) and (2) to analyse the physiological and energetic demands of high-level pommel horse routines (PH routines). The Mmod was developed because VO2 measurements are limited during high-level PH routines. Answering Part 1, nine male artistic gymnasts performed a PH routine where energy costs were calculated from VO2 measurements and then compared with energy costs determined from the HR- VO2 regressions of Mmod`s two additional tests. Using the concordance correlation coefficient (CCC) and Deming regression, Waer (CCC = 0.955), Wpcr (CCC = 0.999), and Wtotal (CCC = 0.990) show substantial to almost perfect validity without constant or proportional bias. Data from eight further gymnasts performing a high-level PH routine and a graded exercise test (GXT), as well as four data sets from Part 1, were used to determine physiological and energetic demands using Mmod. VO2 and HR during PH routines reached 86.1% and 90.4% of the maximal values during GXT. Wpcr was 47.0%, anaerobic lactic energy contribution (Wblc) was 29.7%, and Waer was 23.3% of Wtotal required during PH routines. Summarising the energetic demands of high-level PH routines, they are mainly anaerobic, where Wpcr provides the largest energy share. Waer provides a substantial part of Wtotal and should therefore also be specifically trained.